Training of Paramedical Personnel. Understanding priorities in treatment of diarrhea - Jon E. Rohde (Indonesian Pediatric Society, 1974)
Training of medical personnel must emphasize the importtance of dehydration, its diagnosis, recognition, prevention and treatment. Maintenance of body hydration is the key to therapy for cholera, amoebiasis, toxin producing E. coli, measles, lactose intolerance, acute food poisoning, dengue hemorrhagic fever, viral enteritis, heat stoke; the list is almost endless. Management is basically the same for all.